2016
DOI: 10.1111/1750-3841.13361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrocolloids (Dietary Fibers) on Lipid Digestion of Protein‐Stabilized Emulsions: Comparison of Neutral, Anionic, and Cationic Polysaccharides

Abstract: The impact of dietary fibers on lipid digestion within the gastrointestinal tract depends on their molecular and physicochemical properties. In this study, the influence of the electrical characteristics of dietary fibers on their ability to interfere with the digestion of protein-coated lipid droplets was investigated using an in vitro small intestine model. Three dietary fibers were examined: cationic chitosan; anionic alginate; neutral locust bean gum (LBG). The particle size, ζ-potential, microstructure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 61 publications
5
19
0
Order By: Relevance
“…TSG may also interact with the intestinal components (bile salts, lipase molecules, calcium ions, and lipolysis products); thus, lipid digestion reduced. 10 These results were in agreement with previous findings, [22][23][24] which reported that hydrocolloids may potentially influence lipid digestion by the following various mechanisms: (i) interaction with bile salts, lipase molecules, calcium ions, and lipolysis products; (ii) alteration in flocculation/ coalescence of the oil droplets; (iii) protective stabilization layers covering oil droplets; and (iv) raising the macro-viscosity of digestive systems. The released fatty acid content was lowest (17.5%) in the emulsion containing TSG at 100 g kg −1 of all the emulsion samples.…”
Section: Rheological Properties Of Emulsion During In Vitro Digestionsupporting
confidence: 91%
“…TSG may also interact with the intestinal components (bile salts, lipase molecules, calcium ions, and lipolysis products); thus, lipid digestion reduced. 10 These results were in agreement with previous findings, [22][23][24] which reported that hydrocolloids may potentially influence lipid digestion by the following various mechanisms: (i) interaction with bile salts, lipase molecules, calcium ions, and lipolysis products; (ii) alteration in flocculation/ coalescence of the oil droplets; (iii) protective stabilization layers covering oil droplets; and (iv) raising the macro-viscosity of digestive systems. The released fatty acid content was lowest (17.5%) in the emulsion containing TSG at 100 g kg −1 of all the emulsion samples.…”
Section: Rheological Properties Of Emulsion During In Vitro Digestionsupporting
confidence: 91%
“…The interpolymeric gel network around the emulsion droplets formed by electrostatic interactions could serve as a strong mechanical barrier at the oil/water interface ( Wijaya et al., 2018a , Wijaya et al., 2018b , Wijaya et al., 2019 ). In addition, the complexation of proteins with non-digested polysaccharides like pectin might also hinder the disruption of the droplet's surface by pepsin in the stomach ( Qin et al., 2016 ). Hence, intact droplets remained after gastric digestion, proven by the evidence of efficient lipid digestion in HIPE-complexes compared to MCT oil due to a larger surface area to volume ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Different hydrocolloids may influence the digestion of emulsified lipids by means of various mechanisms e.g. binding to various intestinal components, altering the aggregation state of the oil droplets, forming protective coatings around lipid droplets, or increasing the macroscopic viscosity of gastrointestinal fluids (McClements et al, 2008;Qin et al, 2016;Borreani et al, 2019). In addition, it can be concluded that lipid digestion may potentially be influenced by oil droplet size which influences the surface area available for lipase adsorption, macroscopic viscosity of the systems which affects mass transport, and the nature of the hydrocolloids/emulsifiers used in emulsions which influences interfacial phenomena (Borreani et al, 2019).…”
Section: Controlmentioning
confidence: 99%